Efficient and low-cost temperature automated system for aquariums in fry hatcheries using control algorithms - Macedo, Julio; Díaz, Enrique; Gutiérrez, Ricardo; Marín, William (Revista de Ciencias Sociales, 2023)
The purpose of this research is aimed to bring an alternative solution for the raising of fry in aquatic ponds, through the control and monitoring of water temperature, in order to optimize their development and growth, regardless of the habitat where they are located, improving the production of fish for mass consumption even in places where the climate is not suitable for their raising. The above-mentioned control and monitoring was carried out through the cost-effective Atmega328P microcontroller that make easier its configuration and implementation. This type of research is applied because it gives solution to the problem in optimize the fry raising in aquariums and was divided into the following stages for temperature control: first, the sensor measures the temperature and compares it with a mobile application baseline; second, the water temperature is stabilized by the electronic thermostat; finally, the water temperature is conditioned to get a healthy habitat for the fry. All of this is executed remotely through an application created to be used from a cell phone. Concluding, the right parameters are found to stabilize the water temperature effectively.